Soybean for combating hidden hunger and better human health - Ali, Nawab (Indian Farming, 2015)
Soybean crop fixes about 100 kg of atmospheric nitrogen to the soil, partly used by it and the balance is left in the soil for the next crop. Thus it enriches the soil too. Beyond hiqh quality macro-nutrients such as good quality protein, (40%), unsaturated fatty acids rich oil (20%) and complex carbohydrates (23%); soybean also contains biological nutraceutical ingredients namely isoflavonoids, tocopherols lecithin, biopeptides, and other micronutrients which provide protective effects against cardiovascular diseases, cancers, diabetes, osteoporosis and menopausal problems. Soyfoods and beverages are free from cholesterol and lactose and suit to the poorest of the poor on account of economic and health benefits and to the richest of the rich because of health benefits. Indian population is predominantly vegetarian and their diet is lacking in terms of quantity and quality of protein. Moreover, pulses, the major source of protein for vegetarians have become very costly (Rupees 300/kg of protein). Proteins from livestock sources costÂ Rupees 500-1200/kg of proteins. In such a situation, soybean is a good alternative because it is a very rich source of quality protein at an affordable cost (Rupees75-100/kg of protein) by one and all and can easily meet the protein requirement of vegetarian diet and partly replace protein in non-vegetarian diet making it more healthy at lesser cost. Hence, the use of 30-50g of carefully processed soybean in daily diet helps to combat the hidden hunger (micronutrient malnutrition) and save the country from huge human and economic losses amounting to approximately 2% of the total GDP. Overall, soybean is an environment, animal and human friendly crop needed for better global health.